Sortase A‐mediated site‐specific labeling of camelid single‐domain antibody‐fragments: a versatile strategy for multiple molecular imaging modalities. (5th May 2016) - Massa, Sam; Vikani, Niravkumar; Betti, Cecilia; Ballet, Steven; Vanderhaegen, Saskia; Steyaert, Jan; Descamps, Benedicte; Vanhove, Christian; Bunschoten, Anton; van Leeuwen, Fijs W. B.; Hernot, Sophie; Caveliers, Vicky; et al.
Abstract : A generic site‐specific conjugation method that generates a homogeneous product is of utmost importance in tracer development for molecular imaging and therapy. We explored the protein‐ligation capacity of the enzyme Sortase A to label camelid single‐domain antibody‐fragments, also known as nanobodies. The versatility of the approach was demonstrated by conjugating independently three different imaging probes: the chelating agents CHX‐A"‐DTPA and NOTA for single‐photon emission computed tomography (SPECT) with indium‐111 and positron emission tomography (PET) with gallium‐68, respectively, and the fluorescent dye Cy5 for fluorescence reflectance imaging (FRI). After a straightforward purification process, homogeneous single‐conjugated tracer populations were obtained in high yield (30–50%). The enzymatic conjugation did not affect the affinity of the tracers, nor the radiolabeling efficiency or spectral characteristics. In vivo, the tracers enabled the visualization of human epidermal growth factor receptor 2 (HER2) expressing BT474M1‐tumors with high contrast and specificity as soon as 1 h post injection in all three imaging modalities. These data demonstrate Sortase A‐mediated conjugation as a valuable strategy for the development of site‐specifically labeled camelid single‐domain antibody‐fragments for use in multiple molecular imaging modalities. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Camelid single‐domain antibody‐fragments were labeled chemoenzymatically by Sortase A resulting in homogeneous imaging tracers. The conjugation of different imaging probes allowed tumor visualization in multiple imaging modalities, with high contrast as soon as 1 h post‐injection.